ONLINE CUSTOMER ENGAGEMENT AND RELATIONSHIP BETWEEN SOCIAL MEDIA AND ONLINE SHOPPING - Narayan Mahapatra, Satya; Kumar, Prince (International Journal of Psychosocial Rehabilitation, 2020)
This study assesses 521 respondents about the frequency of purchases from the top online shopping platform. Analyzes the negative experience and customer engagement towards the review perception and other online connects between customer and brand, such as social media. Customers are asked to rank the significant aspects/features related to online shopping engagement. Among six, the easy return policy is considered the number one priority by the majority of the customers. Faster responses to the queries, complaints, and other related concerns are ranked sixth by the majority. If a customer has gone through a bad or negative experience with the brand, more than 9% of the respondents will write about the experience on the brand’s platform and social media platform, which shows excellent opportunity for a strong engagement bond, which leads to a higher customer lifetime value.